Survival of Toddler with Aortoesophageal Fistula after Button Battery Ingestion. (5th October 2021) - Gibbs, Hannah; Sethia, Rishabh; McConnell, Patrick I.; Aldrink, Jennifer H.; Shinoka, Toshiharu; Williams, Kent; Jatana, Kris R.
Abstract : Button batteries (BBs) are found in many households and are a source of esophageal foreign body in the pediatric population. Upon ingestion, significant caustic injury can occur within 2 hours leading to tissue damage and severe, potentially fatal sequelae. Aortoesophageal fistula (AEF) is a rare complication that nearly always results in mortality. We report a rare case of a toddler who developed an AEF after BB ingestion and survived following staged aortic repair. There should be a high index of suspicion for this complication with the history of BB ingestion and presence of hematemesis, hemoptysis, or melena.